Psychometric Evaluation of the Persian Version of the Tinnitus Cognitions Questionnaire - Maryam Sadeghijam; Sahand Rahimi Pour; Zeinab Hasanpour; Iman Hamraz (Auditory and Vestibular Research)
Background and Aim: Cognitive Behavioral Therapy (CBT) is the only evidence-based and method for tinnitus management. To assess a patient’s progress during and after CBT, an assessment tool such as a questionnaire is needed. Since there is no validated tool available in Iran for this purpose, this study aims to investigate the psychometric properties of the Persian version of the Tinnitus Cognition Questionnaire (P-TCQ). Methods: The TCQ was first translated to Persian based on the international quality of life assessment protocol. participants were 102 tinnitus patients and 7 audiologists. After translation and data collection, psychometric properties (content validity, face validity, construct validity, criterion validity, reliability) of the P-TCQ were evaluated. Results: The Content Validity Ratio (CVR) and Item-Content Validity Index (I-CVI) values were higher than the minimum acceptable values (0.74 and 0.79, respectively). Item-level Face Validity Index (I-FVI) and average of Scale-level Face Validity Indexes (S-FVI) were in a range of 0.8-0.96 and 0.88–0.90, respectively, all of which were higher than the acceptable value of 0.7. Furthermore, fit indices had higher than the acceptable values and showed the good fit of the confirmatory factor abalysis model. There was a positive correlations between the TCQ total scores and the tinnitus handicap inventory (r=0.60) and hospital anxiety and depression scale (r=0.61), indicating acceptaiuoble criterion validity. Furthermore, Cronbach’s alpha coefficient and the intraclass correlation coefficient showed that the TCQ has acceptable reliability. Conclusion: The P-TCQ is a valid and reliable questionnaire to evaluate the cognitive aspects of tinnitus in the Iranian samples.